A course in ordinary differential equations - Swift, Randall J.; Wirkus, Stephen Allen 1971- (Chapman & Hall/CRC, 2007)
A Course in Ordinary Differential Equations, Second Edition teaches students how to use analytical and numerical solution methods in typical engineering, physics, and mathematics applications. Lauded for its extensive computer code and student-friendly approach, the first edition of this popular textbook was the first on ordinary differential equations (ODEs) to include instructions on using MATLAB®, Mathematica®, and Maple™. This second edition reflects the feedback of students and professors who used the first edition in the classroom